Racial disparities in emergency general surgery: Do differences in outcomes persist among universally insured military patients?. Issue 5 (May 2016) - Zogg, Cheryl K.; Jiang, Wei; Chaudhary, Muhammad Ali; Scott, John W.; Shah, Adil A.; Lipsitz, Stuart R.; Weissman, Joel S.; Cooper, Zara; Salim, Ali; Nitzschke, Stephanie L.; Nguyen, Louis L.; Helmchen, Lorens A.; et al.
Abstract : BACKGROUND: Racial disparities in surgical care are well described. As many minority patients are also uninsured, increasing access to care is thought to be a viable solution to mitigate inequities. The objectives of this study were to determine whether racial disparities in 30-/90-/180- day outcomes exist within a universally insured population of military-/civilian-dependent emergency general surgery (EGS) patients and ascertain whether differences in outcomes differentially persist in care received at military versus civilian hospitals and among sponsors who are enlisted service members versus officers. It also considered longer-term outcomes of EGS care. METHODS: Five years (2006–2010) of TRICARE data, which provides insurance to active/reserve/retired members of the US Armed Services and dependents, were queried for adults (≥18 years) with primary EGS conditions, defined by the AAST. Risk-adjusted survival analyses assessed race-associated differences in mortality, major acute care surgery-related morbidity, and readmission at 30/90/180 days. Models accounted for clustering within hospitals and possible biases associated with missing race using reweighted estimating equations. Subanalyses considered restricted effects among operative interventions, EGS diagnostic categories, and effect modification related to rank and military- versus civilian-hospital care. RESULTS: A total of 101, 011 patients were included: 73.5% white, 14.5% black, 4.4% Asian, and 7.7% other. Risk-adjusted survival analyses reported a lack of worse mortality and readmission outcomes among minority patients at 30, 90, and 180 days. Major morbidity was higher among black versus white patients (hazard ratio [95% confidence interval): 30 days, 1.23 [1.13–1.35]; 90 days, 1.18 [1.09–1.28]; and 180 days, 1.15 [1.07–1.24], a finding seemingly driven by appendiceal disorders (hazard ratio, 1.69–1.70). No other diagnostic categories were significant. Variations in military- versus civilian-managed care and in outcomes for families of enlisted service members versus officers altered associations, to some extent, between outcomes and race. CONCLUSIONS: While an imperfect proxy of interventions is directly applicable to the broader United States, the contrast between military observations and reported racial disparities among civilian EGS patients merits consideration. Apparent mitigation of disparities among military-/civilian-dependent patients provides an example for which we as a nation and collective of providers all need to strive. The data will help to inform policy within the Department of Defense and development of disparities interventions nationwide, attesting to important differences potentially related to insurance, access to care, and military culture and values. LEVEL OF EVIDENCE: Prognostic and epidemiologic study, level III Abstract : Supplemental digital content is available in the text.